Islamic thought from voices of resurgent Islam to the reformist voices of Islam: an analysis of new trends and themes in the Muslim world - Ali, Mohd Mumtaz (Institute of Islamic Studies, University of the Punjab, Pakistan, 2023)
In recent decades there has been the emergence of a few new trends such as modern Islam, progressive Islam, liberal Islam, civilizational Islam, moderate Islam, and the Voices of the Reformist Islam. All these trends have been presented as the trends of Islamic thought. The themes of these trends seem to be different from the themes of Islamic thought. It appears that the premises of these new trends seem to be different from the Islamic thought. It is assumed that the Islamic thought is generally based on the Islamic worldview and the Quran and Sunnah. The aim of this paper is to investigate and examine the views of those scholars who advocate the Voices of Reformist Islam for the betterment of Muslims of the world with those of the Voices of Resurgent of Islam. This paper will focus only on reformist Islam and follow the method of content analysis and examine the trend of reformist Islam. It will help readers to determine the nature of Islamic thought and those of new trends in so-called Islamic thought.